Navigating digital learning: Autonomy among EFL students in Indonesia - Ribahan, Ribahan; Muslimin, Afif Ikhwanul (Edelweiss Applied Science and Technology, 2025)
This study investigates the autonomy of EFL students in Indonesia in the context of digitalized education, focusing on their autonomy levels, influencing factors, and challenges. A structured Likert-scale questionnaire was administered to 272 second and third-year English Department students at a public university in central Indonesia. Descriptive statistics were employed to analyze the data and interpret the findings. The results reveal a high level of learner autonomy, particularly in accessing and utilizing digital platforms and resources for English language learning. Key factors that enhance autonomy include the accessibility and adaptability of digital learning materials, the integration of tasks within the curriculum that foster independence, and the facilitative role of lecturers in supporting self-directed learning through technology. Despite these positive outcomes, challenges persist. Students reported difficulties in maintaining focus, managing the overwhelming availability of digital resources, and overcoming technical issues such as unstable internet connectivity. These findings underscore the importance of strengthening digital infrastructure, providing clear guidance on resource selection, and enhancing students’ self-regulation skills to support autonomous learning further. This research offers valuable insights for educators and policymakers, contributing to the development of digital learning environments that empower students to become independent learners while addressing the challenges associated with digital education.